A 2020 vision for food, agriculture, and the environment in Latin America - Garrett, James L. (International Food Policy Research Institute, 1995)
This is a thoughtful statement representing a genuine Latin American perspective of the goals and strategies relating to food, agriculture, and the environment as we head toward the year 2020. This document represents a synthesis of documents prepared by three working groups participating in a workshop on Latin America, jointly sponsored by IFPRI, the Centro Internacional de Agricultura Tropical (CIAT) and the Instituto Interamericano de Cooperación para la Agricultura (IICA), in Cali, Colombia, March 20–22, 1995.